Glut-1 is a promising target for atp depletion on diabetic energy deficiency syndrome - Purwanto, Bambang; Harjanto, Harjanto; Asnar, Elyana (Folia Medica Indonesiana, 2017)
Diabetes is a metabolic syndrome which characterized with insulin insensitivity, lack of GLUT-4 membrane presentation and ATP deficiency. ATP is needed for substrate phosphorylation, signalling pathways, protein translation and cellular survival. Since GLUT-1 was discovered as alternative glucose transporter on muscle membrane, some studies started to investigate it more. This study aimed to investigate GLUT-1 presentation on diabetes muscle membrane of rat model in time. Diabetes was obtained from a 50 mg/kg B.W of streptozotocin intra peritoneal injection on rat. We found that GLUT-1 presentation increased significantly in time of diabetic stages. It correlated negatively with GLUT-4 presentation and mortality. Eccentric downhill running on diabetic rat model improved GLUT-1 presentation and blood glucose level. It was promising for diabetes management therapy at the future.